4‐(1‐Amino‐5‐aminotetrazolyl)methyleneimino‐3‐methylfuroxan and Its Derivatives: Synthesis, Characterization, and Energetic Properties. Issue 7 (28th January 2014) - Tang, Yongxing; Yang, Hongwei; Shen, Jianhua; Wu, Bo; Ju, Xuehai; Lu, Chunxu; Cheng, Guangbin
Abstract: The condensation reaction of 4‐formyl‐3‐methylfuroxan with 1, 5‐diaminotetrazole led to 4‐(1‐amino‐5‐aminotetrazolyl)methyleneimino‐3‐methylfuroxan (1 ) in high yield. Its structure was confirmed by an X‐ray diffraction study. 4‐(1‐Amino‐5‐nitriminotetrazolyl)methyleneimino‐3‐methylfuroxan (2 ) was obtained through the nitration of1 with 100 % HNO3 . The nitrogen‐rich salts of2 with bases such as 1‐amino‐1, 2, 3‐triazole (3 ), 4‐amino‐1, 2, 4‐triazole (4 ), and 3‐amino‐1, 2, 4‐triazole (5 ) were synthesized and characterized by IR, Raman, and NMR spectroscopy and elemental analysis. In addition, the structures of2, 4, and5 were further confirmed by single‐crystal X‐ray diffraction analyses. Compound5 decomposes at 183 °C, whereas3 and4 are less stable and decompose at 139 and 164 °C, respectively. The heats of formation, detonation parameters, and impact sensitivity of1 –5 were investigated by theoretical and experimental methods. Abstract : The synthesis of 4‐(1‐amino‐5‐aminotetrazolyl)methyleneimino‐3‐methylfuroxan from 3‐methyl‐4‐formylfuroxan and 1, 5‐diaminotetrazole yields a thermally stable energetic compound. Its nitroiminotetrazole derivative exhibits high positive heats of formation and good detonation performance. Three nitrogen‐rich energetic salts combine moderate thermal stabilities with acceptable sensitivities.